Investigating the relationship between population growth and temperature change in Nabire and Paniai Regencies - Faqi, Ekky Amiral; Wibawa, Leo Arie (Indonesian Journal of Applied Environmental Studies, 2023)
Regional development is a priority programme of the government of the Republic of Indonesia. The region that has received significant development is the province of Papua. The form of development in Papua Province is the division of a new autonomous region (DOB). The formation of new autonomous regions encourages development in newly created areas, especially in urban areas. Cities that are increasingly developing can trigger the flow of urbanization so that the population increases. Increasing population affects climate parameters, especially air temperature. Temperature is expected to increase as a result of an increase in the number of urban residents and the imbalance of energy in and out of the earth. This study aims to determine the effect of population on variations in temperature in Nabire and Paniai Regencies. The data used are annual average, minimum, and maximum temperature data at the Nabire and Paniai Meteorological Stations. The data is displayed in graphical form, and the correlation is calculated to be analyzed descriptively. The results of the study show that there is a strong correlation between population growth and an increase in average and minimum average temperatures. While the average maximum temperature has a weak relationship to population growth. Pembangunan daerah merupakan program prioritas pemerintah Republik Indonesia. Wilayah yang mendapat pembangunan signifikan adalah Provinsi Papua. Bentuk pembangunan di Provinsi Papua adalah pemekaran daerah otonom baru (DOB). Pembentukan daerah otonom baru mendorong pembangunan di daerah pemekaran, khususnya di perkotaan. Kota yang semakin berkembang dapat memicu arus urbanisasi sehingga jumlah penduduk semakin meningkat. Pertambahan jumlah penduduk mempengaruhi parameter iklim khususnya suhu udara. Suhu diperkirakan akan meningkat akibat bertambahnya jumlah penduduk perkotaan dan ketidakseimbangan energi yang masuk dan keluar bumi. Penelitian ini bertujuan untuk mengetahui pengaruh jumlah penduduk terhadap variasi suhu di Kabupaten Nabire dan Paniai. Data yang digunakan adalah data suhu rata-rata, minimum, dan maksimum tahunan di Stasiun Meteorologi Nabire dan Paniai. Data ditampilkan dalam bentuk grafik, dan korelasinya dihitung untuk dianalisis secara deskriptif. Hasil penelitian menunjukkan adanya korelasi yang kuat antara pertumbuhan penduduk dengan peningkatan suhu rata-rata dan minimum rata-rata. Sedangkan rata-rata suhu maksimum mempunyai hubungan yang lemah terhadap pertumbuhan penduduk.